2023
DOI: 10.3390/curroncol30070498
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Cutaneous Immune-Related Adverse Events (irAEs) Induced by Immune Checkpoint Inhibitors

Abstract: Over the past few decades, immune checkpoint inhibitors (ICIs) have emerged as promising therapeutic options for the treatment of various cancers. These novel treatments effectively target key mediators of immune checkpoint pathways. Currently, ICIs primarily consist of monoclonal antibodies that specifically block cytotoxic T-lymphocyte antigen 4 (CTLA-4), programmed cell death 1 (PD-1), programmed cell death-ligand 1 (PD-L1), and lymphocyte activation gene 3 protein (LAG-3). Despite the notable efficacy of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 128 publications
0
8
0
Order By: Relevance
“…According to previous reports, the relationship between immunosuppressive drugs and skin-related AEs may be explained by the activation of the immune system and inflammatory response. Downregulation of the PD-1/ PD-L1 pathway could cause T lymphocytes to release cytotoxic factors such as perforin and granzyme, which results in damage to the skin of affected cells (20). However, in our case, the skin necrosis was still outside the scope of our understanding of the immune mechanisms of ICI-induced cutaneous AEs.…”
Section: Discussionmentioning
confidence: 71%
“…According to previous reports, the relationship between immunosuppressive drugs and skin-related AEs may be explained by the activation of the immune system and inflammatory response. Downregulation of the PD-1/ PD-L1 pathway could cause T lymphocytes to release cytotoxic factors such as perforin and granzyme, which results in damage to the skin of affected cells (20). However, in our case, the skin necrosis was still outside the scope of our understanding of the immune mechanisms of ICI-induced cutaneous AEs.…”
Section: Discussionmentioning
confidence: 71%
“…There is speculation in some studies that the interference with checkpoint molecules may disrupt the delicate balance between peripheral tolerance and the protective role of keratinocytes against damage. 96 This may result from the difference in the incubation period of SJS/TEN induced by anticancer drugs compared to that caused by non-anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Both conditions exhibit elevated expression of inflammatory chemokines, cytotoxic mediators like perforin and granzyme B, and apoptosis-promoting molecules such as Fas Ligand. 96 Especially, TNF-α has been identified in the plasma and blister fluids of patients affected by SJS/TEN. It appears to act as a potential inducer of keratinocyte apoptosis in the context of SJS/TEN.…”
Section: Discussionmentioning
confidence: 99%
“…Skin toxicity is the most common adverse reaction associated with immunotherapy, with PD-1/Programmed Death-Ligand 1 (PD-L1) inhibitors inducing skin toxicity in 30-40% of cases, including rashes and pruritus [40]. However, most skin adverse reactions are mild to moderate and typically resolve without special treatment; severe skin reactions are relatively rare [39]. Previous research has found that the occurrence of skin-related adverse reactions may be a strong predictive factor for the outcomes of treatments for various malignant tumors [24].…”
Section: Lung Patients Encounter Various Clusters Throughout Immunoth...mentioning
confidence: 99%